The role of influencers on the fashion purchase intention of China Generation Z consumers - ZHU, JIAQI (2020)
As social media is becoming more common, social media has grown a part of life for Generation Z, born into the rapid development of network technology. Therefore, social media has displayed a vital marketing platform for fashion brands and marketers, while influencers in social media have become an emerging marketing model. Influencers establish stable relationships with consumers on social media and create a bridge between consumers and fashion trends to affect consumers' purchase intentions. This study investigates the influencers' role in Chinese Generation Z consumers' purchasing intentions in the fashion industry. To examine this, the existing literature on influencer marketing, the role of influencers in the social media and fashion industry and the theory of consumer behavior have been analyzed. Besides, the Generation Z group has been specially studied, which has more special characteristics than other generations. Considering that influencer marketing is a relatively new research field for China, there has not been a large number of studies to evaluate the effectiveness of influencers for Chinese generation Z consumers. This research mainly discusses how influencers affect purchase intentions and why Chinese Generation Z consumers are affected from consumers' perspective. Through the use of qualitative analysis research methods and thematic research, the interviewees are Chinese consumers who fully conform to Generation Z's characteristics. The research results point that influencers influence Chinese generation Z consumers' purchase intention from the four factors of trustworthy, expertise, similarity, and likability, making generation Z consumers more willing to search for fashion products recommended by influencers before buying. Simultaneously, social media's background has caused young Chinese consumers to have a strong dependence on social media. Coupled with the universal network society, they are always affected inadvertently. At the same time, it also analyzes the personal characteristics of Chinese Generation Z consumers. Their lack of opinion and herd mentality makes them more susceptible to influencers. However, the final result shows that the purchasing intention of Chinese generation Z consumers will be affected by the influencers. However, they will also focus on their actual needs and refer to ordinary consumers' shopping feedback a lot because the phenomenon of generalization and commercialization causes consumers to produce a little advertising resistance. Finally, discuss the practical implication further.